A Critique and Review on the Book Islamic Management (Models and Obstacles to its Realization in Society and Organizations) - Gholamreza Godarzi; Mansooreh Moeini Korbekandi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this article is to review and critique the book Islamic Management (Models and Obstacles to its Realization in Society and Organizations). First, the book is evaluated in terms of method and then in terms of content and structure. Also, the extensible points of the book are mentioned in order to enrich the book and open other fields of research. The method of evaluation and critique of this work is citation-analytical and in accordance with the proposed model by the Council for the Study of Humanities Texts and Books in the context of the general introduction, the form and content of the work are examined. This work suffers from a lack of logical order and coherence of content, content inaccuracy, content defects and errors. The technical quality of the work is good and the general rules of writing have been observed. Despite these, the formal weaknesses of the work are simple book cover design, ‌simple page layout, failure to observe the proportion of the volume of the seasons, ‌excessive detail attached to the book, lack of attractive tables, and ack of list of tables, charts, and figures. In general, the analysis of the content of the academic books can provide the potential strengths and weaknesses of these books for the modification and possible change of content and form, in accordance with the set goals and scientific principles to the planners and authors of academic books.